MODEL PENGAMBILAN KEPUTUSAN DALAM PEMBANGUNAN WISATA KULINER PINGGIRAN SAWAH (PIRSA) DESA BILA RIASE - Muhammad Ikbal; Lukman Lukman; Selfiani Selfiani (Jurnal Studi Ilmu Pemerintahan, 2021)
Village Head Decision Making Model in the Development of Pirsa Culinary Tourism in the Village of If the Riase District of Pitu Riase District Sidenreng Rappang in 2020. This study aims to find out how the Village Head Decision Making Model in the Development of culinary tourism in the Village of PIRSA if Riase and to find out what approach was taken by the Village Head in making decisions PIRSA culinary tourism development activities in the Village If Riase. The population of this study was 34 stakeholders and a sample of 34 people. The sampling technique used is the saturated sampling technique. This type of research is quantitative descriptive. Data collection techniques are observation, questionnaire (questionnaire), and literature. Data analysis techniques use descriptive statistics. The results showed that the percentage of each indicator can be seen that the development of PIRSA culinary tourism in the fact, experience, intuition, logic, and system analysis approach that is 40-60% is categorized unfavorably in the development of culinary tourism.